2018
DOI: 10.1186/s12906-018-2400-9
|View full text |Cite
|
Sign up to set email alerts
|

Maoberry (Antidesma bunius) ameliorates oxidative stress and inflammation in cardiac tissues of rats fed a high-fat diet

Abstract: BackgoundChronic fat-rich diets consumption is increased risk associated with cardiovascular diseases (CVD). Prevention or reduction the progression of cardiac tissue deterioration could benefit in CVD. This study aimed to examine the effects of maoberry (Antidesma bunius), a antioxidant-rich tropical fruit, supplementation on oxidative stress and inflammation in cardiac tissues of rats fed a high-fat diet (HFD).MethodsThe male rats orally received HFD with maoberry extract doses of 0.38, 0.76 or 1.52 g/kg or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 45 publications
2
19
1
Order By: Relevance
“…The environmental conditions are controlled in order to reduce or get rid of animal distress. Our previous studies reported that Maoberry extract could benefit against hypercholesterolemia and cardiovascular disease risk factors by antioxidant and anti-inflammation properties [8, 9]. The current study further demonstrates the contributions of Maoberry extract on fat metabolism in liver tissue.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The environmental conditions are controlled in order to reduce or get rid of animal distress. Our previous studies reported that Maoberry extract could benefit against hypercholesterolemia and cardiovascular disease risk factors by antioxidant and anti-inflammation properties [8, 9]. The current study further demonstrates the contributions of Maoberry extract on fat metabolism in liver tissue.…”
Section: Discussionsupporting
confidence: 77%
“…Synergistic interactions of those active ingredients available in Maobery extract have the opportunity to improve the fat metabolism in the liver tissues fed a high-fat diet. In addition to improving fat metabolism, Maoberry extract from our previous studies also showed a reduction of oxidative stress and inflammation in heart tissues [8]. Therfore, this can confirm the ability of strong antioxidant activity that is possessed by Maoberry extract.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Further, WT hearts had significantly more inducible ventricular tachycardia than NOX2 KO hearts after HFD. Part of the arrhythmic effect of NOX2 is due to activation of CaMKII, which phosphorylates the RyR2 channels [ 108 , 109 ]. This causes increased calcium leakage from the SR, which worsens mitochondrial function and promotes arrhythmias [ 27 , 77 ].…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%